MicroRNA-302/367 Cluster Impacts Host Antimicrobial Defense via Regulation of Mitophagic Response Against Pseudomonas aeruginosa Infection - Huang, Ting; Pu, Qinqin; Zhou, Chuanmin; Lin, Ping; Gao, Pan; Zhang, Xiuyue; Chu, Yiwen; Yue, Bisong; Wu, Min (Frontiers in Immunology, 2020)
Mitophagy has recently been implicated in bacterial infection but the underlying mechanism remains largely unknown. Here, we uncover a role of microRNA-302/367 cluster in regulating mitophagy and its associated host response against bacterial infection. We demonstrate that miR-302/367 cluster expression was significantly increased after Pseudomonas aeruginosa infection. Enhanced expression of miR-302/367 cluster accelerated the mitophagic response in macrophages, thus increasing clearance of invading P. aeruginosa by regulating production of reactive oxygen species (ROS), while application of miR-302/367 cluster inhibitors decreased bacterial clearance. Blocking mitophagy with siRNA against mitophagy receptor prohibitin 2 (PHB2) reduced the effect of miR-302/367 cluster on induction of mitophagy and its-associated P. aeruginosa elimination. In addition, we found that miR-302/367 cluster also increased bacterial clearance in mouse model. Mechanistically, we illustrate that miR-302/367 cluster binds to the 3’-untranslated region of nuclear factor kappa B (NF-κB), a negative regulator of mitophagy, accelerated the process of mitophagy by inhibiting NF-κB. Furthermore, inhibition of NF-κB in macrophages attenuated the ROS or cytokines production and may reduce cell injury by P. aeruginosa infection to maintain cellular homeostasis. Collectively, our findings elucidate that miR-302/367 cluster functions as potent regulators in mitophagy-mediated P. aeruginosa elimination and pinpoint an unexpected functional link between miRNAs and mitophagy.